Knowledge Regarding Modifiable Risk Factors of Coronary Atherosclerosis Heart Diseases in Kathmandu Municipality - Khadka, M (Nepalese Heart Journal, 2013)
Background Progressive urbanization and adoption of the “western” lifestyle contributes to the rising burden of cardiovascular disease in the developing world Coronary Atherosclerotic Heart Disease is no longer confined by geographical area or socioeconomic boundary. The prevalence of Coronary Atherosclerotic Heart Disease is increasing in Nepal. Knowledge is an important pre-requisite for implementing both primary and secondary preventive strategies for cardiovascular diseases. This investigation attempts to quantify knowledge of modifiable risk factors of Coronary Atherosclerotic Heart Disease among sample population in Kathmandu metropolitan city. Methods Community based cross-sectional descriptive study design using quantitative method of study was conducted in ward no 5 of Kathmandu out of 35 wards. Selection was done by simple random technique (lottery method). Total house hold serial number of selected ward was identified from election commission record section and data was collected using systemic random sampling. The household head aged 18 years and above was taken as representative sample (n= 196). Standard questionnaire was used to interview participants. The risk factors specifically included smoking, hypertension, elevated cholesterol levels, diabetes mellitus and obesity. Results The mean age (SD) of the 196 participants was 51.26 (13.56) years. Of the participants only 22% had good level of knowledge regarding modifiable risk factors of Coronary Atherosclerotic Heart Disease. This study showed that majority of the respondent lack predefined good level of knowledge regarding modifiable risk factors of Coronary Atherosclerotic Heart Disease. 85.2%, 61.73%, 40.31%, 28.6%, 17.86% correctly identified hypertension, obesity, cholesterol, smoking and diabetes mellitus respectively as modifiable risk factor of Coronary Atherosclerotic Heart Disease. Stud y found association of good level of knowledge in male participants (p=0.006), Brahmin cast (p=0.001), living in nuclear family (p= 0.041), ex-smoker (p=0.06), doing regular exercise ( p= 0.006). Conclusion This study call for efforts such as targeted public health education to increase the level of knowledge about the modifiable risk factors of heart disease. DOI: http://dx.doi.org/10.3126/njh.v9i1.8347 Nepalese Heart Journal Vol.9(1) 2012 pp.37-42